Proposed Relationships Between Climate, Biological Soil Crusts, Human Health, and in Arid Ecosystems - Marieke L. Ramsey; Daniel R. Kollath; Anita J. Antoninka; Bridget M. Barker (GeoHealth)
Abstract Biological soil crusts (or biocrust) are diminutive soil communities with ecological functions disproportionate to their size. These communities are composed of lichens, bryophytes, cyanobacteria, fungi, liverworts, and other microorganisms. Creating stabilizing matrices, these microorganisms interact with soil surface minerals thereby enhancing soil quality by redistributing nutrients and reducing erosion by containment of soil particles. Climatic stressors and anthropogenic disturbances reduce the cover, abundance, and functions of these communities leading to an increase of aeolian dust, invasive plant establishment, reduction of water retention in the environment, and overall poor soil condition. Drylands are the most degraded terrestrial ecosystems on the globe and support a disproportionately large human population. Restoration of biocrust communities in semi‐arid and arid ecosystems benefits ecosystem health while decreasing dust emissions. Dust abatement can improve human health directly but also indirectly by reducing pathogenic microbe load circulating in the ambient air. We hypothesize that biocrusts not only reduce pathogen load in the air column but also inhibit the proliferation of certain pathogenic microbes in the soil. We provide a review of mechanisms by which healthy biocrusts in dryland systems may reduce soil‐borne pathogens that impact human health. Ecologically sustainable mitigation strategies of biocrust restoration will not only improve soil conditions but could also reduce human exposure to soil‐borne pathogens.